2011
DOI: 10.1002/app.35049
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation behavior of conducting carbon black reinforced ethylene acrylic elastomer vulcanizates

Abstract: ABSTRACT:The dielectric relaxation characteristics of conductive carbon black (CCB) reinforced ethylene acrylic elastomer (AEM) vulcanizates have been studied as a function of frequency (10 1 -10 6 Hz) at different filler loading over a wide range of temperatures (30-120 C). The effect of filler loadings on the dielectric permittivity (e 0 ), loss tangent (tan d), complex impedance (Z*), and electrical conductivity (r ac ) were studied. The variation of e 0 with filler loading has been explained based on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…The improvement of σ AC with the addition of nanoparticles can be explained according to the relative tendency of hopping of charge carriers in PVA-Ni 0.5 Zn 0.5 Fe 2 O 4 nanocomposites is higher than that in pure PVA. This high increment in conductivity can be ascribed to the increase in the formation of continuous conductive pathways inside the PVA network [46]. At high temperatures and frequencies, the AC conductivity becomes less frequency dependence which follows the data reported in [47].…”
Section: Resultssupporting
confidence: 84%
“…The improvement of σ AC with the addition of nanoparticles can be explained according to the relative tendency of hopping of charge carriers in PVA-Ni 0.5 Zn 0.5 Fe 2 O 4 nanocomposites is higher than that in pure PVA. This high increment in conductivity can be ascribed to the increase in the formation of continuous conductive pathways inside the PVA network [46]. At high temperatures and frequencies, the AC conductivity becomes less frequency dependence which follows the data reported in [47].…”
Section: Resultssupporting
confidence: 84%
“…This behaviour is observed by several Fig. 10 a Dielectric loss (tan δ e ) and b magnetic loss (tan δ m ) parameters of alloy resin paint composites A1, A2, A3 and A4 over [6][7][8][9][10][11][12][13][14][15][16][17][18] authors for the composites containing various types of filler materials (18,19). In the similar line, the observed less dielectric loss in composite sample A4 may be due to the decrease of interfacial polarization at higher loading of Fe-Si-Al alloy particles.…”
Section: Resultssupporting
confidence: 53%
“…7). To obtain microwave absorption properties of composite coatings, the complex permittivity and permeability values have been calculated by Nicolson and Ross algorithm using S-parameters measured through waveguide transmission line technique over MW frequency range (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The experimental set up for EM parameter measurement is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the concentration increases, the fillers start to form a three dimensional network through the matrix, giving rise to a huge increase in the electrical conductivity. The idea of the sub-percolative strategy is to maintain the dielectric character of the matrix, by working at concentrations below the percolation threshold, while taking advantage of the increase in the dielectric permittivity.The search for high permittivity elastomer composites has been pursued with different conductive fillers, from metal[115][116][117] to carbon-based micro particles[118][119][120]. Thus, for instance, in 2009, Stoyanov et al reported the dielectric properties of a poly-styrene(coethylene-co-butylene-co-styrene) (SEBS) matrix loaded with carbon black (CB) as conducting filler[118].…”
mentioning
confidence: 99%